Probabilidade de ocorrência de deficiência hídrica na cultura do girassol na região central do Rio Grande do Sul - Maldaner, Ivan Carlos (2012)
In Brazil over recent years the interest increased on the sunflower cultivation. Sunflower yield can be decreased by water deficit. To solve this problem, is necessary to calculate the probable water deficit in critical sunflower sub-phases and in the whole development cycle at different sowing dates. The objective of this study was to determine the probable duration values of sub-phases and the developmental cycle and get sowing dates with lower risk of water deficit and the occurrence probability in different levels of water deficit during the developmental sub-phases of sunflower crop sown at different sowing dates, considering the water storage capacity in different soils in the Central Region of Rio Grande do Sul. Also determine the probability of occurrence of water stress for different years classified as the El Niño Southern Oscilation (ENSO). Crop development was simulated using the thermal time method, for 14 sowing dates, from August until mid-February, for every year during the period from 1968 to 2011, covered by database of Meteorological Station of Santa Maria, RS. For calculating the water deficit, the 13 soils were grouped into six groups with similar water storage capacity (CAD) and infiltration capacity. The water deficit was calculated from daily water balance. Data analysis consisted of analysis of variance, means comparison tests and analysis of probability distribution for the variables: duration of crop developmental sub-phases and the whole developmental cycle of the sunflower, water deficit in the sub-phases and whole developmental cycle. The length of the sub-phases and the development cycle of the sunflower crop are variable depending on sowing date. The length of the developmental sub-phases that occur from sowing until flower bud visible of sunflower are higher in the earliest sowing date (01/08). After anthesis, the longer length of developmental sub-phases occurs in the latest sowing (16/02). The lognormal, normal and gamma distributions represent better the development of sunflower to estimate the length of the phases and the whole cycle. At sowing date of 16/12, for 90% probability level, sunflower has the shortest length of the developmental cycle ending the cycle in a maximum of 96 days. The longer length of the sunflower cycle occurs at sowing date of 01/08, which reaches 132 days, at 90% level of occurrence probability. The sowing dates from early October until early November are the ones with the highest water deficit, considering the whole development cycle of the sunflower regardless of soil, a different choice on sowing date reduces the risk and the level of water deficit in sunflower cycle. In the soils in which the water storage capacity is lower, water deficit is greater in sub-phases as in the full cycle of the sunflower compared to other soils and is little variable among the sowing dates. Sunflower Sowings in the first half of August and since December are the ones with the lowest risk occurrence of water deficit during the more critical sub-phase of sunflower crop, at least there are favorable conditions for sowing and initial establishment of plants.